Bacillus subtilis ALBA01 alleviates onion pink root by antagonizing the pathogen Setophoma terrestris and allowing physiological status maintenance - Sayago, Pamela; Juncosa, Florencia; Albarracín Orio, Andrea Georgina; Luna, Dario Fernando; Molina, Gabriela; Lafi, Jorge; Ducasse, Daniel Adrian (Springer, 2020)
The soil-borne pathogen Setophoma terrestris is the causal agent of pink root of onion, one of the most challenging diseases in onion production. Conventional approaches for managing the disease like solarization, soil fumigation and crop rotation have not been proven effective enough. In this work, we evaluated the biocontrol capacity of Bacillus subtilis ALBA01 (BsA01) against S. terrestris, in a highly susceptible onion cultivar, both under greenhouse and field conditions. Disease incidence and severity were evaluated together with growth, photosynthesis among other physiological variables, and yield parameters. When compared with plants infected with the pathogen, those plants co-inoculated with BsA01 showed significantly less damage and levels of biocontrol above 50%. With regard to physiological parameters, plants challenged with S. terrestris and inoculated with BsA01 performed as well as the control non-infected plants revealing a growth promotion effect of BsA01 on onion plants.